Relationship of Parental Involvement with Self-regulation and Academic Achievement of Chinese Primary School Pupils, in Kerian District, Perak - Y.C. Chia; F.D. Hutagalung (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The purpose of this study was to determine the relationship of parental involvement with self-regulation and academic achievement of Chinese primary school pupils, in Kerian District, Perak. This study employed a quantitative correlational design via google forms to obtain data from 100 participants from parents and pupils. The respondents were required to complete three questionnaires- Parental Involvement in Academic Achievement Among primary schools Questionnaire, Self-Regulation Formative Questionnaire, and Academic Achievement Questionnaire-measure parental involvement, self-regulation, and academic achievement respectively. Data received was then analyzed using SPSS 23.0 to find out if there is a correlation between the three variables. The difference in parental involvement among different parents’ education levels and gender differences in self-regulation were also tested. The findings indicated that the type of parental involvement among Chinese primary school pupils was Communication. The level of self-regulation of the pupils was in the intermediate level. Positive and significant correlations were found between parental involvement, self-regulation, and academic achievement. However, there were no significant gender differences in self-regulation. Overall, the role of parental involvement should be taken into full consideration while examining the relationship between children’s self-regulation level and family issues, since it could create a long-lasting impact on a child’s lives.